Development of Assessment Performance Materials Cylinder Students Grade IX SMP Adiwiyata-Based - Vembriliya, Zelmy Adista; Khumaedi, Muhammad; Masrukan, Masrukan (Journal of Research and Educational Research Evaluation, 2019)
The assessment instrument for mathematics performance of Adiwiyata-based cylinder material is not standard, although there are instruments but not yet valid and reliable, and there is no clear rubric to assess learning outcomes. This study aims to develop assessment instruments for cylinder material performance based on adiwiyata class IX students who are valid and reliable. This research method uses Djemari Mardapi model development research with preliminary stages, development, and evaluation. The study of instruments by experts was analyzed using the Aiken's V formula, the reliability of the instrument was based on the agreement of experts with analysis using two way ANOVA and re-analyzed using the Hoyt formula. Construct validity was assessed using exploratory factor analysis, the reliability of the instrument based on field results was analyzed using Cronbach Alpha with the help of SPSS. The performance assessment of cylinder material developed consists of 10 items. The results of the evaluation of the measured content have a value of> 0.3, that the skill instrument developed is valid. The reliability results based on expert agreement show a value of 6 0.6, which means experts agree in assessing. Data analysis in the field test can be seen from the results of Kaiser Meyer Olkin (KMO) which shows KMO values> 0.5 so that the instrument items can be analyzed further. There are three factors formed from each assessment, each item in each factor has a value of loading factor> 0.3 while the three factors are preparation, implementation, and final results. The results of reliability in the field have a value of> 0.6 so that the instruments developed are consistent in carrying out the assessment. The results of this study can be used as a guideline for teachers in junior high schools in conducting a performance assessment of adiwiyata-based cylinder material.